The world of Jesus: first-century Judaism in crisis - Riches, John Kenneth (Understanding Jesus today, 1990)
This book examines the social, economic, political, and cultural context of first-century Judaism. Precipitated by the coming of the Romans during the previous century, Judaism experienced a crisis of cultural erosion in the first century A.D. The author first describes the ways in which foreign domination threatened the Jewish community - for example, by causing a migration away from the countryside into cities. He then discusses how various groups of Jews tried to preserve their cultural identity through their definitions of Jewishness and through the ethical codes they devised. Groups examined include the Pharisees, the Sadducees, the Zealots, the Essenes, and John the Baptist and his followers. The author locates Jesus' teaching in relation to the teachings of these groups, arguing that Jesus was deeply committed to the values of the Jewish tradition even while he proposed radical change that he believed would bring renewal.